Biofunctionalized Hybrid Magnetic Gold Nanoparticles as Catalysts for Photothermal Ablation of Colorectal Liver Metastases - White, Sarah B. (Radiology, 2017)
PURPOSE: To demonstrate that anti-MG1 conjugated hybrid magnetic gold nanoparticles (HNPs) act as a catalyst during photothermal ablation (PTA) of colorectal liver metastases, and thus increase ablation zones. MATERIALS AND METHODS: All experiments were performed with approval of the institutional animal care and use committee. Therapeutic and diagnostic multifunctional HNPs conjugated with anti-MG1 monoclonal antibodies were synthesized, and the coupling efficiency was determined. Livers of 19 Wistar rats were implanted with 5 × 10(6) rat colorectal liver metastasis cell line cells. The rats were divided into three groups according to injection: anti-MG1–coupled HNPs (n = 6), HNPs only (n = 6), and cells only (control group, n = 7). Voxel-wise R2 and R2* magnetic resonance (MR) imaging measurements were obtained before, immediately after, and 24 hours after injection. PTA was then performed with a fiber-coupled near-infrared (808 nm) diode laser with laser power of 0.56 W/cm(2) for 3 minutes, while temperature changes were measured. Tumors were assessed for necrosis with hematoxylin-eosin staining. Organs were analyzed with inductively coupled plasma mass spectrometry to assess biodistribution. Therapeutic efficacy and tumor necrosis area were compared by using a one-way analysis of variance with post hoc analysis for statistically significant differences. RESULTS: The coupling efficiency was 22 μg/mg (55%). Significant differences were found between preinfusion and 24-hour postinfusion measurements of both T2 (repeated measures analysis of variance, P = .025) and T2* (P < .001). Significant differences also existed for T2* measurements between the anti-MG1 HNP and HNP-only groups (P = .034). Mean temperature ± standard deviation with PTA in the anti-MG1–coated HNP, HNP, and control groups was 50.2°C ± 7.8, 51°C ± 4.4, and 39.5°C ± 2.0, respectively. Inductively coupled plasma mass spectrometry revealed significant tumor targeting and splenic sequestration. Mean percentages of tumor necrosis in the anti-MG1–coated HNP, HNP, and control groups were 38% ± 29, 14% ± 17, and 7% ± 8, respectively (P = .043). CONCLUSION: Targeted monoclonal antibody–conjugated HNPs can serve as a catalyst for photothermal ablation of colorectal liver metastases by increasing ablation zones. (©) RSNA, 2017